Attendance Management System Using Fingerprint Scanner - Roshazira, Ahmad (UTeM, 2009)
This project is to design and develops a reliable tracking and recording systems based on biometric fingerprint identification used to monitor attendance. Biometric Access Control System also provides the highest level of security available today by eliminative the stolen, transferred and duplicating. It also will eliminate the problems related with manual work associated with paper based and punch card. The systems will be developed with extended GUI by using Microsoft Visual Studio 2005 integrated with Microsoft Fingerprint Reader which stores the login names and passwords in an internal database located in the user's computer. When needed, the device interactively sends the login names and passwords to compatible applications and websites which can be used to perform the login operation automatically. The device could be useful in an office or campus environment.